An Experimental Study of the Properties of Carbon Fiber/Epoxy Composites Mixed with Rubber Granules - Jeremy Jeba Samuel Joseph Jebaraj; Ramadoss Rajendran (International Journal of Polymer Science)
In this research work, the mechanical properties of hybrid composites reinforced with woven carbon fiber mats particulated with natural rubber powders as fillers in the epoxy resin matrix were investigated. The specimens were prepared by the hand-layup process followed by a vacuum bag moulding process. The vacuum moulding reduces the voids or cavities in the hybrid composites. The natural rubber powder was added in different weight proportions (5%, 10%, 15%, and 20%), and carbon fiber is added in 20% for all the specimens. Experiments such as tension testing, flexural testing, water absorption/acid corrosion/base corrosion tests, dynamic mechanical analysis (DMA), and scanning electron microscopic (SEM) analysis were conducted to evaluate the epoxy carbon rubber (ECR) composites. The tensile and flexural test findings demonstrated that the addition of 10% natural rubber particles gave better results as compared with other proportions. The water/acid/base absorption test findings reveal that the ECR composites are not affected by water/acid/base. The DMA teat findings show that ECR composites having 10% natural rubber have higher damping factor, storage, and loss modulus. The SEM analysis shows that ECR hybrid composites with 10% rubber particles contained a uniform distribution of rubber particles over reinforcement, and also, there were no cracks and voids. According to this research findings, ECR hybrid composites with 10% natural rubber particles prepared during the vacuum bag moulding process can be used to prepare aerospace interior components.